EVALUASI PEMBERIAN KOMPENSASI DALAM MENINGKATKAN KINERJA STAF BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA (BPMPD) PROVINSI SUMATERA SELATAN - Fahlevi, Arry Halbadika; Annisa, Annisa (Lentera Ilmu Madani, 2024)
Research titled Giving Compensation Evaluation in Improving Staff Performance CommunityEmpowerment Board and Village Government ( BPMPD ) South Sumatra Province has the goal toevaluate the implementation of the compensation in improving the performance of the staff ofCommunity Empowerment and Governance Village ( BPMPD ) South Sumatra Province . The focus inthis study is the evaluation of Granting Compensation in Improving Staff Performance CommunityEmpowerment Board and Village Government ( BPMPD ) South Sumatra Province which can beanalyzed using the following indicators : Input , include : Human Resources and Funds ; process , include: Employee Earnings and Supplementary Type criteria for Granting Employee Income Supplement ;Output , include : Quality of Work ( Quality of work ) , timeliness ( promptness ) , Initiative ( Initiative ) ,capability ( capability ) and Communication ( Communication) . The method used in this research isdescriptive method with qualitative data analysis techniques . The data was collected by conductinginterviews with key informants who had been assigned . Key Informant who successfully met the Head ofthe Agency, the Agency Secretary , Kasubbag Finance , Personnel and Sub Section 2 of the staff of theAgency for Rural Empowerment and Governance ( BPMPD ) South Sumatra and secondary data in theform of documentation . In the implementation of the Compensation Provision In Improving StaffPerformance Community Empowerment Board and Village Government ( BPMPD ) South Sumatraprovince as a whole has been carried out in accordance with existing regulations and by the Governor ofSouth Sumatra Province Regulation No. 4 of 2013 concerning Income Supplement civil servants and civilservant in the Provincial Government Environment South Sumatra . Agency staff performance VillageCommunity Empowerment and Governance ( BPMPD ) South Sumatra province has seen an increase ofachievement programs and activities carried out in improving the performance of its staff done byconducting education and training or technical assistance related to the implementation of staff duties